PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN PERMAINAN EGRANG UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI ENERGI MEKANIK - Sa’diyah, Lisa Lailatus; Dwikoranto; Setiani, Rahyu (IPF: Inovasi Pendidikan Fisika, 2025)
The aim of this research is to improve students' critical thinking skills through the application of the Problem Based Learning (PBL) model assisted by stilt games on mechanical energy material. The research design uses a Non-equivalent Control Group Design which is classified as a quasi-experimental group. The subjects in this research were students from SMA Negeri 1 Kalitidu class X-3 as the control class and students from class X-4 as the experimental class. The research instrument consists of an implementation observation sheet, a critical thinking skills test sheet, and a student response sheet. The results of this study state that the implementation of the PBL model assisted by stilts has been implemented in the very good category. Critical thinking skills as measured by prerequisite tests, N-Gain, paired t-test and effect size calculations from the experimental class are in the high category. The average response of students in the experimental class was a positive response in the very good category. Significant results related to students' critical thinking skills before and after implementing the PBL model assisted by stilt games on mechanical energy material with an assessment of the implementation and responses of students which were included in the very good category meant that this learning could be continued and developed in physics learning and other learning. Keywords: Critical Thinking Skills, Problem Based Learning, Stilt Games.